2016
DOI: 10.1175/jas-d-15-0244.1
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Convection Parameterization with Markov Chains in an Intermediate-Complexity GCM

Abstract: Conditional Markov chain (CMC) models have proven to be promising building blocks for stochastic convection parameterizations. In this paper, it is demonstrated how two different CMC models can be used as mass flux closures in convection parameterizations. More specifically, the CMC models provide a stochastic estimate of the convective area fraction that is directly proportional to the cloud-base mass flux. Since, in one of the models, the number of CMCs decreases with increasing resolution, this approach mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Davini et al [] showed that stochastic parameterizations in EC‐Earth improve the simulation of tropical rainfall rate distributions and the Madden‐Julian Oscillation, and Wang et al [] found that the scheme of Plant and Craig [] improves the simulated tropical rainfall rate distribution in the NCAR Community Atmosphere Model as well. Dorrestijn et al [], Goswami et al [], and Peters et al [] showed that variants of the stochastic multicloud model of Khouider et al [] improved aspects of tropical variability simulated in different GCMs, and Frenkel et al [] showed similar results in a single‐column model context. Christensen et al [] also found that stochastic physics greatly reduced excessive El Niño variability in the NCAR Community Atmosphere Model, version 4 (CAM4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davini et al [] showed that stochastic parameterizations in EC‐Earth improve the simulation of tropical rainfall rate distributions and the Madden‐Julian Oscillation, and Wang et al [] found that the scheme of Plant and Craig [] improves the simulated tropical rainfall rate distribution in the NCAR Community Atmosphere Model as well. Dorrestijn et al [], Goswami et al [], and Peters et al [] showed that variants of the stochastic multicloud model of Khouider et al [] improved aspects of tropical variability simulated in different GCMs, and Frenkel et al [] showed similar results in a single‐column model context. Christensen et al [] also found that stochastic physics greatly reduced excessive El Niño variability in the NCAR Community Atmosphere Model, version 4 (CAM4).…”
Section: Introductionmentioning
confidence: 99%
“…Such parameterizations have been used in several numerical weather prediction models, including some run operationally, and have been found to improve forecast skill by both increasing the spread of ensemble forecasts and reducing the size of errors of the ensemble mean forecasts [e.g., Buizza et al, 1999;Palmer et al, 2009;Reynolds et al, 2011;Yonehara and M. Ujiie, 2011;Bouttier et al, 2012;Sušelj et al, 2014;Berner et al, 2015;Sanchez et al, 2016]. There are also numerous other promising schemes that have been or are being developed [e.g., Plant and Craig, 2008;Khouider et al, 2010;Bengtsson et al, 2013;Rochetin et al, 2014;Kober et al, 2015;Shutts, 2015;Dorrestijn et al, 2016;Sakradzija et al, 2016;Ollinaho et al, 2017;Peters et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of simplicity, Khouider et al (2010) neglected interactions between lattice sites by making the transition rates R kl depend exclusively on the large-scale predictors-independent on the realizations of X t outside the underlying site x. This simplification enabled the derivation of a coarse-grained stochastic birth-death process for the CAFs associated with each cloud type, in closed form without any further assumptions, and its successful validation and implementation in a hierarchy of climate models (Bergemann et al, 2017;Deng et al, 2015;Dorrestijn et al, 2016Dorrestijn et al, , 2013Frenkel et al, 2012;Goswami et al, 2017aGoswami et al, , 2017bPeters et al, 2013Peters et al, , 2017.…”
Section: The Smcm For the Caf And Its Mean Field Limitmentioning
confidence: 99%
“…The microcells then make random transitions from one state to another according to prescribed probability rules depending on the large-scale state. Various flavors of the SMCM have been successfully implemented and tested in both wave-dynamical models of intermediate complexity and in comprehensive state-of-the-art climate models (Dorrestijn et al, 2016;Frenkel et al, 2012;Goswami et al, 2017a;2017b;Peters et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant progress in developing stochastic schemes over the last decade, primarily for use in medium-range and seasonal ensemble forecasts (e.g. Plant and Craig, 2008;Khouider et al, 2010;Bengtsson et al, 2013;Grell and Freitas, 2013;Dorrestijn et al, 2016;Sakradzija et al, 2016;Ollinaho et al, 2016). These schemes introduce an element of randomness into physical parameterisation schemes to account for the impact of uncertain, unresolved processes on the resolved-scale flow (Palmer, 2012).…”
Section: Introductionmentioning
confidence: 99%